2020
DOI: 10.1007/s12105-020-01127-1
|View full text |Cite
|
Sign up to set email alerts
|

Palatal Erythema with Histological Psoriasiform Pattern: An Enigmatic Oral Finding Shared by a Range of Conditions

Abstract: Long standing, asymptomatic, well-demarcated erythema of the hard palate with a histopathological psoriasiform pattern comprises a challenging diagnosis. We present a series of patients with such clinical and histological findings and discuss the possible diagnoses. We collected all patients with palatal erythematous lesions that had well-documented clinical examination. Excluded were patients with definitive diagnosis of oral infections (e.g. candidiasis), neoplastic/pre-neoplastic lesions, auto-immune diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…HMD is an exceedingly rare disease first described by Witkop et al in 1978, with only several dozen cases reported to date. 2,3 HMD is inherited in a predominantly autosomal dominant manner. 4 The underlying etiology of HMD has historically been attributed to abnormalities in gap junction and desmosome formation, as the culprit gene was considered unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMD is an exceedingly rare disease first described by Witkop et al in 1978, with only several dozen cases reported to date. 2,3 HMD is inherited in a predominantly autosomal dominant manner. 4 The underlying etiology of HMD has historically been attributed to abnormalities in gap junction and desmosome formation, as the culprit gene was considered unknown.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Mucosal lesions have consistent characteristic histopathological findings, including epithelial hyperplasia, dysmaturation, nuclear pleomorphism, increased nuclear-tocytoplasmic ratio, and intracytoplasmic inclusions. 3,4,6 Scalp histopathological findings in HMD are considerably less well characterized. Only a single scalp biopsy specimen, also taken by shave technique, has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…13 The etiology is vague, and the lesion may be an oral manifestation in patients with cutaneous psoriasis, rarely a restricted form of psoriasis, or may be associated with hereditary mucoepithelial dysplasia or other conditions. 12 Palatal lipidophilia is another lesion found in patients with psoriasis that has been described in the literature but not confirmed sufficiently. It is a deposition of lipid deposits on the soft palate and palatine arches, observed as a bounded yellow spot.…”
Section: Changes In the Oral Mucous Membranementioning
confidence: 98%
“…The and superficial tips of connective tissue lined with thinned epithelium). 12 Some authors suggest qualifying the lesion as a manifestation of erythema migrans. 13 The etiology is vague, and the lesion may be an oral manifestation in patients with cutaneous psoriasis, rarely a restricted form of psoriasis, or may be associated with hereditary mucoepithelial dysplasia or other conditions.…”
Section: Changes In the Oral Mucous Membranementioning
confidence: 99%
See 1 more Smart Citation